Purification and characterization of recombinant acetohydroxyacid synthase from Heamophillus influazae - Linh, Le Thuy; Nam, Vu Tuan; Dung, Le Tien (Academia Journal of Biology, 2016)
Acetohydroxyacid synthase (AHAS) presents only in plants and microorganisms. The enzyme catalyzes the first common step in the biosynthesis of branch chain amino acids (BCAAs), including isoleucine, leucine and valine. AHAS is also a potential target for controlling Haemophilus influenzae. In this study, the recombinant catalytic subunit of AHAS from H. influenza (Hin-AHAS) was expressed in Escherichia coli. The purified Hin-AHAS protein exhibited a molecular weight of approximately 63 kDa on SDS-PAGE gel. The apparent Vmax and Km values of the purified Hin-AHAS were determined to be 0.236 U/mg protein and 2.503 mM pyruvate, respectively. Two inhibitors of plant AHAS, namely ethoxysulfuron (ETS) and pyrazosulfuron ethyl, were shown to inhibit Hin-AHAS in a non-competitive manner with the IC50 values of 90.14 µM and 376.6 µM, respectively. This result showed that the purified enzyme can be used for screening of inhibitors against Hin-AHAS.